Reservation through image visualization - Rusli M.E.B.; Yusof A.M.; Ibrahim N. (2023)
In tourism industry, reservation or booking through the Internet is now so common; it is becoming the practice among the big or small industry players. However, what is missing and lacking is the concept of virtual imaging that represent the ongoing transaction. For this paper, the focus is visualizing real time reservation for an island-based vacation area. Up to now, most of the information is conveyed to the customers through plain boring old text or through verbal explanation given by service provider through phone or emailing system. Major frustration is caused by not knowing the exact location of the reserved facility within the particular area. So, this paper will discuss in detail the weakness of current reservation process that can be avoided by applying an improved multimedia management technology through graphics visualization technique. 2006 IEEE.